In situ forming stereocomplexed and post-photocrosslinked acrylated star poly(ethylene glycol)-poly(lactide) hydrogels. (September 2017) - Buwalda, Sytze J.; Dijkstra, Pieter J.; Feijen, Jan
Graphical abstract: Highlights: Acrylate-endcapped, amide-linked PEG-PDLA and PEG-PLLA star block copolymers. Tandem gelation via stereocomplexation followed by UV photopolymerization. Injectable hydrogels with excellent mechanical properties and hydrolytic stability. A mechanism for the formation and degradation/dissolution of the gels is proposed. Abstract: Biodegradable acrylate end-group functionalized poly(ethylene glycol)-poly(lactide) (PEG-PLA) star block copolymer hydrogels were formed by the consecutive physical gelation through stereocomplexation of star shaped PEG-(PLLA)8 and PEG-(PDLA)8 enantiomers and UV photopolymerization. The 8-armed PEG-PLA star block copolymers were prepared by ring opening polymerization of lactide onto an amine end-group functionalized PEG with a molecular weight of 20 kg/mol using stannous octoate as a catalyst. The degree of polymerization of the PLA blocks was 12 lactyl units and the end hydroxyl groups were reacted with acryloyl chloride to give the required acrylate end groups. Aqueous solutions of enantiomeric mixtures of the PEG-(PLA)8 macromonomers formed physically crosslinked hydrogels above a critical gel concentration of 4 w/v%. Subsequent photopolymerization at 365 nm in the presence of Irgacure 2959 resulted in gels with improved mechanical properties and hydrolytic stability. With 40% polymer mass loss after 45 d in vitro, these hydrogels show excellent resistance against hydrolytic degradation and dissolution, which is believed to result from the combination of stable amide linkages between the PEG and PLA blocks and the high physical and chemical crosslink density owing to the star architecture.